Implementación de un sistema de adquisición de datos de energía producida en una estación fotovoltaica de 560w para La obtención de las pérdidas de energía. - Moscoso Villarroel, Carlos Miguel (2023)
Environmental factors such as temperature, dirt, and shadows, as well as losses in electrical components, can affect the efficiency of a photovoltaic system. Achieving an optimal installation would result in preventing most of the losses. To quantify the losses of a photovoltaic system, a solar energy data acquisition system can be implemented. The aim of this proposed technology is the implementation of an energy data acquisition system to determine the losses by installing equipment that measures radiation, ambient temperature, cell temperature, voltage, and current of the photovoltaic panels. Additionally, the PowerStudio SCADA software will be used, allowing the visualization of energy production and real-time operation through the design of an HMI. The study arises from the lack of knowledge about the energy losses that occur in photovoltaic stations, which is why there is a need to use electrical devices to visualize the generated energy data. The methodology used is application-based, employing bibliographic methods, inductive and deductive field studies. The results obtained during its operation have shown that the losses in the electrical generation system were an average of 92.71% on the first day, 93.61% on the second day, and for the third day, the average loss was 93.14%. After conducting field tests for three days at defined time points, the system's loss percentage was evaluated. The results show an average loss percentage of 93.15% in the system during its study.